Shear strengthening of RC beams using aluminum plates: An experimental work. (10th October 2019) - Fayed, Sabry; Basha, Ali; Hamoda, Ahmed
Highlights: Shear resistance of RC beams was studied experimentally. Strengthening of RC beams using steel plates and FRP sheets. Using aluminum plates in strengthening of RC beams has been investigated. Good agreement between experimental results and prediction procedure. Abstract: Strengthening of the reinforced concrete (RC) beams using Aluminum plates (APs) is the most recent method. In this research, the shear strengthening of the RC beams using APs was studied experimentally. The experimental program consisted of twenty four RC beams (1/2 scale) that were tested under four-point bending flexural experiments. All beams had the same dimensions and the same internal reinforcement. Different shear strengthening techniques using APs were carried out. APs were fixed on the beam sides to enhance the shear strength vertically, inclined by 45°, diagonally and horizontally. Influence of the spacing, height and quantity of the APs was studied. The effect of the APs on the behaviour of RC beams with low compression strength of concrete was investigated. All AP techniques succeeded in enhancing the shear capacity and some of them changed the failure mode to flexural type. The highest ratio of increase of the shear strength was 76.8%. AP techniques had not increased the shear strength of the RC beams made from the weak concrete.